Role of Oximes in Organophosphorous Poisoning - Editor (GMC Patiala Journal of Research and Medical Education, 2024)
Poisoning both intentional and accidental are huge contributor to mortality and morbidity throughout the world. The most common cause of poisoning in developing countries like India are pesticides, the reason being agriculture-based economics and among them organophosphorus constitutes the largest bulk of pesticides. Standard treatment involves supportive measurements, administration of intravenous atropine and oxime to counter acetylcholinesterase inhibition at the synapse.[1] However, the usefulness of oximes, such as pralidoxime and obidoxime has been challenged over the past 20 years by physicians in many parts of the world who have failed to see benefit in their clinical practice. But there are various reasons for that as the published methodology in such studies is unclear and another study conducted in Sri Lanka shows that 70% patients had ingested dimethyl compounds, where ageing of enzyme occurs at much early stage and hence, ineffectiveness of oximes.